POLA MAKAN DENGAN KEJADIAN KEKAMBUHAN PADA KLIEN GASTRITIS - Palangi, Thio Tri Fanti; Ispriantari, Aloysia (Indonesian Journal Of Empirical Nursing Sciences, 2025)
Introduction: Gastritis remains a prevalent health issue globally. Although not life-threatening, it significantly impacts an individual’s quality of life, primarily due to unhealthy lifestyle choices. Maintaining health eating habits plays a crucial role in preserving the digestive system’s health. This study aimed to analyze the relationship between dietary patterns and the recurrence pf gastritis. Methods: A cross-sectional design was employed in this study, involving 43 respondents at the Duono Community Health Center in West Halmahera Regency. Data were collected using questionnaires on dietary consumption patterns and the incident of gastritis. Statistical analysis was then performed using the Chi-Square test. Results: The study revealed a significant association between dietary patterns and the recurrence of gastritis (p<0.005). Conclusion: based on these findings, health care professionals at the Community Health Center, especially nurses, it is highly recommended to more proactive in educating the community about the importance of maintaining health eating habits to reduce the incidence of gastritis recurrence.